Insight, secrecy, beasts, and beauty: struggles over the making of a Ghanaian documentary on 'African traditional religion' - Witte, Marleen de (Postscripts: The Journal of Sacred Texts & Contemporary Worlds, 2005)
Since the liberalization of the Ghanaian media in 1992, audiovisual representation has become crucial in the struggle over religion and culture. This article examines the neo-traditionalist Afrikania Mission’s struggles with audiovisual media in the context of a strong Pentecostal dominance in Ghana’s religious and media landscape. It argues that the study of religion in an era of mass media cannot be limited to reli-gious doctrine and content. One must also take into account matters of style and format associated with audiovisual representation. This article shows how new media opportunities and constraints have pushed Afrikania to adapt its strategies of access-ing the media and its styles of representation. Adopting dominant media formats such as the documentary, the news item, and the spectacle involves a constant struggle over revelation and concealment. It also entails the neglect of much of the spiritual power that constitutes African religious traditions. The question of how to represent spiritual power through audiovisual media occupies many religious groups, but the question of its very representability seems to be especially pressing for Afrikania.
free
Keywords: Afrikania Mission; Christianity and African religions; Documentary films; Films – Religious aspects; Ghana.; Pentecostal churches